Transitions in diatom assemblages and pigments through dry and wet season conditions in the Red River, Hanoi (Vietnam) - Thi Duong; Hai Nguyen; Thi Le; Trung Nguyen; Thi Tran; Nhu Le; Dinh Dang; Thi Vu; Virginia Panizzo; Suzanne McGowan (Plant Ecology and Evolution, 2019)
Background and aims – Biomonitoring is an important tool for assessing river water quality, but is not routinely applied in tropical rivers. Marked hydrological changes can occur between wet and dry season conditions in the tropics. Thus, a prerequisite for ecological assessment is that the influence of ‘natural’ hydrological change on biota can be distinguished from variability driven by water quality parameters of interest. Here we aimed to (a) assess seasonal changes in water quality, diatoms and algal assemblages from river phytoplankton and artificial substrates through the dry-wet season transition (February–July 2018) in the Red River close to Hanoi and (b) evaluate the potential for microscopic counts and high-performance liquid chromatography (HPLC) analysis of chlorophyll and carotenoid pigments for biomonitoring in large tropical rivers.Methods – River water (phytoplankton) and biofilms grown on artificial glass substrates were sampled monthly through the dry (February–April) to wet (May–August) season transition and analysed via microscopic and HPLC techniques.Key results – All phototrophic communities shifted markedly between the dry and wet seasons. Phytoplankton concentrations were low (c. thousands of cells/mL) and declined as the wet season progressed. The dominant phytoplankton taxa were centric diatoms (Aulacoseira granulata and Aulacoseira distans) and chlorophytes (Scenedesmus and Pediastrum spp.), with chlorophytes becoming more dominant in the wet season. Biofilm diatoms were dominated by Melosira varians, and areal densities declined in the wet season when fast-growing pioneer diatom taxa (e.g. Achnanthidium minutissimum, Planothidium lanceolatum) and non-degraded Chlorophyll a concentrations increased, suggesting active phytobenthos growth in response to scour damage. Otherwise, a-phorbins were very abundant in river seston and biofilms indicating in situ Chlorophyll a degradation which may be typical of tropical river environments. The very large range of total suspended solids (reaching > 120 mg/L) and turbidity appears to be a key driver of photoautotrophs through control of light availability.Conclusions – Hydrological change and associated turbidity conditions exceed nutrient influences on photoautotrophs at inter-seasonal scales in this part of the Red River. Inter-seasonal differences might be a useful measure for biomonitoring to help track how changes in suspended solids, a major water quality issue in tropical rivers, interact with other variables of interest.